1981
DOI: 10.1002/jpln.19811440507
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatverarmung des wurzelnahen Bodens und Phosphataufnahme von Mais und Raps

Abstract: Zusammenfassung -SummaryAus der Verteilung des isotopisch austauschbaren Phosphats wurde mit Hilfe der Phosphatdesorptionskurve festgestellt, daR die Phosphatkonzentration der Bodenlosung im Wurzelhaarbereich von 0,8 auf 0,03mg P/1, d. h. auf 4 % des Ausgangswertes, absinkt.Aus der Zunahme der Phosphatverarmungszone mit der Zeit wurde die Phosphataufnahme einzelner Maiswurzelabschnitte fur verschiedene Zeitintervalle errechnet. Danach erfolgt die P-Aufnahme 3-5 Tage lang in annahernd maximaler Rate, obwohl die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(38 citation statements)
references
References 18 publications
(4 reference statements)
4
29
2
3
Order By: Relevance
“…Even more markedly, the biphasic growth of the depletion zone became obvious when the time-course of the concentration of EP at the root surface was followed: While during the first phase EP was decreased by 70%, it increased again during phase two. The extent of the initial drop is quite in good agreement with data reported by Hendricks et al, (1981).…”
Section: The Dynamics Of the P-depletion Zone Around The Root: Uptakesupporting
confidence: 92%
“…Even more markedly, the biphasic growth of the depletion zone became obvious when the time-course of the concentration of EP at the root surface was followed: While during the first phase EP was decreased by 70%, it increased again during phase two. The extent of the initial drop is quite in good agreement with data reported by Hendricks et al, (1981).…”
Section: The Dynamics Of the P-depletion Zone Around The Root: Uptakesupporting
confidence: 92%
“…The rhizosphere, i.e. the portion of soil influenced by the root concerning P, was in our experiment only 1 mm, which is close to values of Hendriks et al (1981) but smaller than 2-4 mm of Hedley et al (1994). The amount of soil volume within the range of the P depletion is much higher for cylindrical than for planar root surfaces.…”
Section: Effect Of Plant Age On P Fraction Depletionsupporting
confidence: 61%
“…This relatively low exploitation of the alkali-soluble P i , even though the ´planar` root causes a strong concentration decrease in soil solution (Claassen and Steingrobe, 1999;Hendriks et al, 1981), may be related to the following. For one, only part of the alkali-soluble P is isotopically exchangeable (Bühler et al, 2002) and thereby plant available and furthermore, 30-40% of this isotopically exchangeable P would not be plant available because its equilibrium P concentration in soil solution is below Figure 3 shows that maize only depleted the alkali soluble P i (NaHCO 3 -P i and NaOH-P i ) in both soils.…”
Section: Plant Availability Of Different P Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In apparent contrast to the notion that P becomes depleted with time in the rhizosphere (Hendriks et al, 1981;Hinsinger et al, 2011b;Wang et al, 2005), we observed elevated concentrations of labile P fractions in soil adjacent to roots as compared to soil farther away from the roots in the highdensity samplings. Likely reasons for this effect are P solubilization by root exudation and overriding P uptake by roots (Hinsinger et al, 2011b).…”
Section: Discussioncontrasting
confidence: 99%